Monika Piątkowska as a Researcher in Sport Sciences and Sport Management - Piątkowska Monika; Kosiewicz Jerzy (Sciendo, 2017)
This is the fifth article of the cycle of portraits of the members of the Editorial Board and Editorial Advisory Board of the journal Physical Culture and Sport. Studies and Research. These members are social scientists who research the issue of sport. Among them, there are many world-class professors, rectors, and deans of excellent universities, founders, presidents, and secretaries-general of continental and international scientific societies and editors of high-scoring journals related to social sciences focusing on sport. The idea of presenting portraits of individual editors of our writings has already gained recognition in the Far East. Editor-in-Chief Young Lee of the International Journal of Eastern Sports & Physical Education has decided to introduce Corner of Editors, which will also present all members of the Editorial Board.